2012
DOI: 10.1016/j.bbamem.2012.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol perturbs lipid organization in models of stratum corneum membranes: An investigation combining differential scanning calorimetry, infrared and 2H NMR spectroscopy

Abstract: Ethanol is used in a variety of topical products. It is known to enhance the permeability of the skin by altering the ability of the stratum corneum (SC) intercellular membranes to form an effective barrier. In addition, ethanol and other alcohols are key components of antiseptic gels currently used for hand wash. Using infrared and deuterium NMR spectroscopy as well as calorimetry, we have investigated the effect of ethanol on a model membrane composed of lipids representing the three classes of SC lipids, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 59 publications
1
39
0
Order By: Relevance
“…30) In addition, ethanol has been reported to extract and fluidize SC lipids. [31][32][33] Dimethyl sulfoxide has been shown to change keratin conformation and also interact with SC lipids. 34,35) However, the interactions of these CPEs with SC lipids was mainly on the polar head region.…”
Section: Discussionmentioning
confidence: 99%
“…30) In addition, ethanol has been reported to extract and fluidize SC lipids. [31][32][33] Dimethyl sulfoxide has been shown to change keratin conformation and also interact with SC lipids. 34,35) However, the interactions of these CPEs with SC lipids was mainly on the polar head region.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of the skin with some chemicals such as acetone and ethanol causes barrier disruption due to extraction of SC lipids [71,72]. Imokawa et al [73] reported that the application of 5% SDS aqueous solution to human forearm skin resulted in a chapped and scaly SC without any inflammatory reaction.…”
Section: Factors Affecting the Composition And Organization Of Sc Lipidsmentioning
confidence: 99%
“…Ethanol-induced oxidative stress is the result of the combined impairment of antioxidant defenses and the production of reactive oxygen species (ROS) by the mitochondrial electron transport chain, the alcohol-inducible cytochrome P450 (CYP) 2E1 and activated phagocytes and hydroxyethyl free radicals generated during alcohol metabolism by CYP 2E1 [6,9]. ROS, in turn, are able to damage or cause complete degradation of essential complex molecules in the cells, including lipids, proteins and DNA [6,10,11,12]. …”
Section: Introductionmentioning
confidence: 99%